The influence of halal tourism destination performance, memorable experience and perceived value on revisit intention of Sharia Eco-Parks Tankayo Malalo - Fauzan, Muhamad; Engriani, Yunita (Marketing Management Studies, 2024)
This research aims analize the influence of Halal Tourism Destination Performance, Memorable Experience and Perceived Value on Revisit Intention of Sharia Eco-Parks Tankayo Malalo. Population of this study were tourists who had visited the Sharia Eco-Parks Tankayo Malalo tourist attraction in Tanah Datar Regency, West Sumatra. The number of samples used in this research was 190 respondents. Data was collected by distributing questionnaires online via google form and data processing was carried out using IBM SPSS Statistics 25 software. The results of this research show that (1) Halal Tourism Destination Performance has a positive and significant effect on Revisit Intention. This means that the better the Halal Tourism Destination Performance, the greater a person's intention to visit again. (2) Memorable Experience has a positive and significant effect on Revisit Intention. This means that the better the Memorable Experience, the greater a person's intention to visit again. (3) Perceived Value has a positive and significant effect on Revisit Intention. This means that the better the Perceived Value, the greater a person's intention to visit again.